Lower foraging efficiency in immatures drives spatial segregation with breeding adults in a long-lived pelagic seabird. (December 2015) - Fayet, Annette L.; Freeman, Robin; Shoji, Akiko; Padget, Oliver; Perrins, Chris M.; Guilford, Tim
Abstract : Competition and, ultimately, adaptive specialization are the major ecological forces behind spatial segregation in foraging distributions, and are commonly driven by size-related differences in competitiveness between individuals of different sex, age or social status. However, such segregation can also be observed in long-lived monomorphic species, often between immature and breeding individuals. In many of these species, individuals often forage in patchy and potentially unpredictable environments in which resources can be spread over large scales and be difficult to find, and efficient foraging may require advanced cognitive skills (for example in navigation and memory). Particularly in species with deferred breeding, experience rather than size may be an important driver of segregation and may lead to differences in competitiveness between young and old, but whether there is a relationship between age, foraging efficiency and spatial segregation has never been properly investigated. Here we tested this hypothesis by simultaneously tracking individuals at different life stages in a long-lived seabird, the Manx shearwater, Puffinus puffinus, during a period of central-place foraging around the colony, to investigate spatial segregation, and by measuring foraging efficiency by combining an ethoinformatics approach and mass gain. We found substantial spatial segregation between immature and breeding adults. Compared with adults, immatures gained less mass per unit of time spent foraging and foraged in less productive waters, suggesting lower foraging efficiency, probably because of inexperience. Highlights: We simultaneously track immature and breeding shearwaters during foraging trips. There is substantial spatial segregation between breeding adults and immatures. Immatures have a lower foraging efficiency than breeding adults. Immatures exploit less productive waters than breeding adults.